Childhood socioemotional development and growth mindset preceding schizophrenia: case–control study using prospectively collected data - Javiera Vasquez-Nuñez; José Conejeros; Camila Díaz-Dellarrossa; Cristian Mena; UNDURRAGA FOURCADE, JUAN PABLO; Alfonso Gonzalez-Valderrama; Ruben Nachar; Susana Claro; Eduardo A. Undurraga; Nicolas A. Crossley (Royal College of Psychiatrists, 2026)
Background Understanding premorbid socioemotional trajectories in schizophrenia is crucial for early identification and potential primary prevention. Studies in adults with schizophrenia suggest similar socioemotional premorbid difficulties, but are limited by their retrospective design. Aims To contribute new insights into the premorbid socioemotional characteristics of schizophrenia, beyond the biases of retrospective studies, this research investigates three educational socioemotional dimensions in children who later developed the disorder. Method We conducted a case–control study using prospectively collected data, examining childhood differences in perceived parental support, self-esteem and school motivation, and growth mindset (intelligence can improve through effort) among individuals who later developed schizophrenia ( n = 341) and their classmates ( n = 20 567). We constructed z -normalised indicators based on standardised national tests administered in fourth, eighth and tenth grades in Chile. Mixed linear models accounted for repeated measures and adjusted for educational level, gender, grade point average, school and year. Results Children later diagnosed with schizophrenia reported less parental educational support compared with their classmates ( β = −0.276, 95% CI −0.388 to −0.163). Only girls who later developed schizophrenia reported lower self-esteem and school motivation than their peers ( β = −0.290, 95% CI −0.498 to −0.131). Contrary to our hypothesis, children who later developed schizophrenia showed a higher growth mindset ( β = 0.287, 95% CI 0.077–0.497). Conclusions Our results suggest that premorbid socioemotional characteristics in schizophrenia are detectable in childhood and may vary by gender. These findings highlight the potential of educational settings as platforms for preventive interventions aimed at enhancing parental support and monitoring students’ psycho-emotional well-being, while acknowledging gender-specific developmental trajectories and heterogeneity in premorbid functioning.